2019
DOI: 10.1093/femsec/fiz093
|View full text |Cite
|
Sign up to set email alerts
|

Who eats what? Unravelling microbial conversion of coal to methane

Abstract: Microbial communities in subsurface coal seams are responsible for the conversion of coal organic matter to methane. This process has important implications for both energy production and our understanding of global carbon cycling. Despite the environmental and economic importance of this process, little is known about which components of the heterogeneous coal organic matter are biodegradable under methanogenic conditions. Similarly, little is known about which taxa in coal seams carry out the initial stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…In parallel, exogenous soil_2 can also potentially affect the decomposition and methane production processes of coal seams. For example, increased Sphingomonadales and Propionibacteriales might participate in the degradation of coal organic matter, and the presence of Rhodocyclales and Nitrosomonadales could enhance acetic acid metabolism . Most interestingly, increased orders of Bacillales and Nitrospirales , are often detected in coal seams and participated in the process of methane production.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, exogenous soil_2 can also potentially affect the decomposition and methane production processes of coal seams. For example, increased Sphingomonadales and Propionibacteriales might participate in the degradation of coal organic matter, and the presence of Rhodocyclales and Nitrosomonadales could enhance acetic acid metabolism . Most interestingly, increased orders of Bacillales and Nitrospirales , are often detected in coal seams and participated in the process of methane production.…”
Section: Discussionmentioning
confidence: 99%
“…These sulfate-reducing bacteria can use kerogen as an end-point autoacceptor or shuttle to oxidize acetic acid or other simple fatty acids, which is the key to the degradation of organic matter in coal seams. 18 Meslé et al. 19 pointed that the depletion of bitumen by solvent extraction resulted in an increase in methane volume in some shales, indicating the methanogenic potential of the shale matrix.…”
Section: Introductionmentioning
confidence: 99%
“…To better clarify the specific process of methanogenic coal bioconversion, several studies tried to investigate the interaction mechanism between coal and microbial communities. Vick et al identified the biodegradable components of coal by a native microbial community and the corresponding microorganisms involved in that scenario (Vick et al, 2019). Webster et al evaluated the effect of different chemical oxidative treatments on coal to mimic microbial oxidation, and found that oxidative treatments of coal caused significant changes in chemical profiles compared to untreated coal (Webster et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…), hydrogen, and carbon dioxide, which are then used by methanogens to produce methane (in't Zandt et al, 2017; Wei et al, 2013). The methanogenic coal bioconversion process has important implications for both energy production and our understanding of global carbon cycle (Vick et al, 2019) while a start‐up procedure was necessary and important for the subsequent reactions. The initial stage of coal degradation accounts for great responsibility for the start of bioenergy production and carbon metabolic flux.…”
Section: Introductionmentioning
confidence: 99%